Estudo das atividades antifúngica, antiinflamatória intestinal e antinociceptiva visceral do látex do croton urucurana baill - Gurgel, Luilma Albuquerque (2005)
The red sap (Sangre de Grado) extracted from some Croton species is used in folk medicine for the treatment of cancer, rheumatism, wounds, ulcers, diarrhoea, intestinal colics and to combat infections. The aim of this study was to evaluate a possible antimicrobian activity of the sap extracted from Croton urucurana Baill. (SCU) and its intestinal antiinflammatory and visceral antinociceptive potential. The experimental models used were acetic acid-induced colitis and mesenteric ischemia/reperfusion-induced intestinal injury in rats; acetic acid-induced writhing, cyclophosphamide-induced cystitis and capsaicin-induced visceral pain in mice; and in vitro models to evaluate the antibacterian and antifungal activities of SCU. In the acetic acid-induced colitis, the pretreatment with SCU (200 and 400 mg/kg, r.r.) reducted (p<0,05) the wet weight/length ratio of colonic tissue, the myeloperoxidase and catalase activities and the nitrite production in comparison to control animals. In mesenteric ischemia/reperfusion model the pretreatment with SCU (200 and 400 mg/kg, p.o.) prevented (p<0,01) the increase in the myeloperoxidase and catalase activities and the ischemia/reperfusion-associated increase in nitrite level. The SCU (200 mg/kg, p.o.) also prevented (p<0,001) the depletion in reduced glutathione level in this model. Both doses reduced (p<0,05) the number of acetic acid-induced writhing, the number of capsaicin-induced nociceptive behaviour and the time of visceral pain-related behaviour in cyclophosphamide-induced cystitis in mice. The pretreatment with naloxone (5 mg/kg, i.p.) reverted the SCU (200 mg/kg, p.o.) antinociceptive activity in capsaicin-induced visceral pain model, however, ioimbine (2 mg/kg, i.p.) failed to mitigate in a significant manner, this antinociceptive effect. The SCU antinociceptive activity, in this model, was not potentiated by L-nitro-arginine-methyl esther (20 mg/kg, i.p.) or rutheniun red (3 mg/kg, s.c.). SCU failed to show activity against the bacterias (Staphylococus aureus and Escherichia coli) and yeasts tested (Cândida sp., Trichosporon sp. and Malassezia sp.), although, presented activity against the dermatophytes Trichophyton mentagrophytes, Trichophyton tonsurans, Trichophyton rubrum, Microsporum canis and Epidermophyton floccosum in paper disk diffusion method and showed minimal inhibitory concentration of 1,25 mg/mL for Trichophyton tonsurans and 2,5 mg/mL for the others species. In conclusion, the results of this study suggest that the SCU presents intestinal antiinflammatory activity, possible because of its antioxidant action, visceral antinociceptive activity and antifungal activity against dermatophytes. Its antinociceptive effect is probable dependent of opioid and nitriergic mechanism, with a possible participation of vaniloid receptors without involvement of α2-adrenergic receptors. This results confirm its popular use, and it can be explored as an alternative treatment for dermatophytosis, inflammatory intestinal diseases and functional gastrointestinal disorders.